Optimizing the Smart Pump Drug Library Update Process: An Ongoing Effort at an Academic Medical Center - Courtney Olson; Carin Bouchard (Patient Safety)
Smart infusion pumps with dose-error reduction software and customizable drug libraries have increased the safety of intravenous infusion delivery; however, maintaining the most updated drug library is a multistep process for most infusion pumps, which requires effort and engagement by the end user to activate the latest drug library. Delays in updating the drug library have been shown to impact patient safety. This article reviews steps taken at an academic medical center to improve the drug library update process. Multidisciplinary efforts resulted in improved drug library activation rates; however, despite workflow optimizations and improvements, achieving complete pump fleet library activation in a timely manner after scheduled updates remains challenging.